2010
DOI: 10.1080/01411920902780972
|View full text |Cite
|
Sign up to set email alerts
|

What makes teachers tick? Sustaining events in new teachers’ lives

Abstract: To investigate what keeps teachers motivated on a day-to-day basis, we traced the importance of routinely encountered affective episodes. Significant research on emotions already highlights the relative importance of positive versus negative episodes, the importance of perceived origins of events and the need to differentiate between the frequency and affective intensity of episodes. Survey reports from 749 recently qualified primary teachers in Ireland strongly suggest the absence of positive experiences unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 42 publications
3
45
0
3
Order By: Relevance
“…The importance for pre-service drama teachers having an effective mentor teacher is highlighted in this research, and supports earlier research claiming that an effective mentor is vital in developing pre-service teachers' professional efficacy (Flores & Day, 2006;Harrison, 2008;Langdon, Alexander, Dinsmore, & Ryde, 2012;Morgan et al, 2009). The experiences and perspectives provided by participants, led to the identification of six attributes of an effective mentor teacher for pre-service drama teachers.…”
Section: Professional Collegialitysupporting
confidence: 61%
See 1 more Smart Citation
“…The importance for pre-service drama teachers having an effective mentor teacher is highlighted in this research, and supports earlier research claiming that an effective mentor is vital in developing pre-service teachers' professional efficacy (Flores & Day, 2006;Harrison, 2008;Langdon, Alexander, Dinsmore, & Ryde, 2012;Morgan et al, 2009). The experiences and perspectives provided by participants, led to the identification of six attributes of an effective mentor teacher for pre-service drama teachers.…”
Section: Professional Collegialitysupporting
confidence: 61%
“…Mentor teachers are also key to a positive practicum experience (Ingersoll & Strong, 2011;Moody, 2009;Morgan, Ludlow, Kitching, O'Leary & Clarke, 2009). K. Anderson, Walker and Ralph (2009) suggested that mentor teachers not only play an integral role in building self-efficacy in pre-service teachers, but recommended that mentors adjust their level of support so that it was in harmony with pre-service teachers' confidence and competence to meet challenges.…”
Section: The Importance Of Self-efficacy During Practicummentioning
confidence: 99%
“…In his research on teachers working in inner-city high schools in the United States, Brunetti (2006) defined teacher resilience as 'a quality that enables teachers to maintain their commitment to teaching and teaching practices despite challenging conditions and recurring setbacks ' (2006, p. 813). Over time research has also consistently found that teachers' self-efficacy beliefs as to whether they have the capacity to effectively help children learn and achieve are one of the most important factors influencing teachers' resilient qualities (Kitching et al, 2009;Morgan et al, 2010;Hong, 2012). In this sense, resilient teachers are not survivors in the profession because they 'do more than merely get through difficult emotional experiences, hanging on to inner equilibrium by a thread ' (O'Connell Higgins, 1994, p. 1; see also Gu and Li, 2013).…”
Section: What We Already Knowmentioning
confidence: 99%
“…To develop a research instrument for the study, the researcher needed to adapt some questionnaires from eminent scholar in the field of teacher quality (Adedoyin, 2011;Hacicaferoglu, 2014;Ihmeideh et al, 2010;Smith, 2009;James, 2013;Solomon, 2007;Sowell, 2013 andMorgan, et al, 2010). In this study, teacher knowledge; communication skills; teacher commitment and classroom management are referred to as teacher quality (TQ).…”
Section: Instrumentationmentioning
confidence: 99%